Stereotactic Body Radiation Therapy for the Treatment of Locally Recurrent and Oligoprogressive Non-Small Cell Lung Cancer: A Single Institution Experience - Katz, Leah M.; Ng, Victor; Wu, S. Peter; Yan, Sherry; Grew, David; Shin, Samuel; Colangelo, Nicholas W.; McCarthy, Allison; Pass, Harvey I.; Chachoua, Abraham; Schiff, Peter B. (Frontiers in Oncology, 2022)
Objectives To investigate the efficacy and safety of lung stereotactic body radiation therapy (SBRT) for non-small cell lung cancer (NSCLC) including oligorecurrent and oligoprogressive disease. Methods Single-institution retrospective analysis of 60 NSCLC patients with 62 discrete lesions treated with SBRT between 2008 and 2017. Patients were stratified into three groups, including early stage, locally recurrent, and oligoprogressive disease. Group 1 included early stage local disease with no prior local therapy. Group 2 included locally recurrent disease after local treatment of a primary lesion, and group 3 included regional or well-controlled distant metastatic disease receiving SBRT for a treatment naive lung lesion (oligoprogressive disease). Patient/tumor characteristics and adverse effects were recorded. Local failure free survival (LFFS), progression free survival (PFS), and overall survival (OS) were estimated using the Kaplan Meier method. Results At median follow-up of 34 months, 67% of the study population remained alive. The estimated 3-year LFFS for group 1, group 2, and group 3 patients was 95% (95% CI: 86%-100%), 82%(62% - 100%), and 83% (58-100%), respectively. The estimated 3-year PFS was 59% (42-83%), 40% (21%-78%), and 33% (12%-95%), and the estimated 3-year OS was 58% (41-82%), 60% (37-96%), and 58% (31-100%)), respectively for each group. When adjusted for age and size of lesion, no significant difference in OS, LFFS, and PFS emerged between groups (p > 0.05). No patients experienced grade 3 to 5 toxicity. Eighteen patients (29%) experienced grade 1 to 2 toxicity. The most common toxicities reported were cough and fatigue. Conclusions Our data demonstrates control rates in group 1 patients comparable to historical controls. Our study also reveals comparable clinical results for SBRT in the treatment of NSCLC by demonstrating similar rates of LFFS and OS in group 2 and group 3 patients with locally recurrent and treatment naïve lung lesion with well-controlled distant metastatic disease.